Moral Education Representation in English Elementary School Textbooks Endorsed by the Indonesian Government: An Ontogenetic Analysis of Social Values - Banun Havifah Cahyo Khosiyono; Jamiu Temitope Sulaimon (ELE Reviews: English Language Education Reviews, 2026)
This research explores the representation of social values and their ontogenetic development in English textbooks for Indonesian elementary schools. This research is a critical discourse analysis that adopts a social semiotic approach. It considers social values in textbooks as semantic categories created through intricate semiotic discursive resources. It also provides a clear framework for illustrating how and why values are chosen. An examination of six English textbooks from grades 1 through 6 in elementary school demonstrates how social values shift from the personal (such as maintaining a healthy lifestyle and practicing good hygiene) to the interpersonal (such as showing respect and being courteous) to the altruistic concern for all people. Additionally, the results imply that the textbooks are more focused on teaching good citizens than on developing children’s critical thinking skills. By mapping the 258 social values onto the axis of Judgement (separating Capacity from Propriety) and tracking their ontogenetic progression (how the text constructs the child’s developmental growth), a much sharper tool for critique is gained. Teachers should be more imaginative and cautious when assigning tasks to students, and incorporate characters, particularly social values, into lesson plans and teaching and learning activities.